Antimicrobial resistance in fecal Escherichia coli and Campylobacter spp. from beef cows in western Canada and associations with herd attributes and antimicrobial use - Waldner, Cheryl L. (Can J Vet Res, 2019)
The objectives of this study were to describe the frequency of antimicrobial resistance (AMR) in Escherichia coli and Campylobacter spp. isolates in fecal samples from beef cow-calf herds and to examine the associations between herd management practices, reported antimicrobial use, and AMR. Baseline prevalence data are needed to evaluate the effectiveness of antimicrobial stewardship programs. A pooled fecal sample, representing 20 cows, was collected from each of 107 herds during pregnancy testing. In the 305 recovered E. coli isolates (maximum 3 per herd), resistance to ≥ 1 antimicrobial was identified in 12 isolates [4%, 95% confidence interval (CI): 2% to 7%] from 105 herds (11%, 95% CI: 7% to 19%). The most common resistances identified in E. coli isolates were to tetracycline (3%) and to both streptomycin and sulfisoxazole (3%). Only 1 E. coli isolate was resistant to an antimicrobial of very high importance to human health — amoxicillin/clavulanic acid. However, 2 E. coli isolates had intermediate susceptibility to ciprofloxacin. Resistance to 1 antimicrobial was identified in 16 of 87 Campylobacter spp. isolates (18%, 95% CI: 11% to 28%) from 87 herds. Resistance to tetracycline was reported in 15% of Campylobacter spp. isolates and to nalidixic acid in 3.4%. Herds in which cows were treated with florfenicol were more likely to have E. coli resistance to ≥ 2 antimicrobials (OR 7.1, 95% CI: 1.1 to 57, P = 0.03). Herds with calf mortality of > 5% were more likely to have E. coli with resistance to streptomycin and sulfisoxazole [odds ratio (OR): 7.8, P = 0.03]. The results of this study are consistent with previous reports from western Canada and provide a starting point for designing an ongoing antimicrobial surveillance program.